Agricultural knowledge networks in rural Europe, 1700-2000 - Segers, Yves 1970-; Molle, Leen van 1953- (The Boydell Press, 2022)
An examination of how farming expertise could be shared and extended, over four centuries
Title from publisher's bibliographic system (viewed on 13 Sep 2022)
Keywords: Geschichte 1700-2000; Communication in agriculture / Europe / History / 18th century; Communication in agriculture / Europe / History / 19th century; Communication in agriculture / Europe / History / 20th century; Agricultural innovations / Europe / History / 18th century; Agricultural innovations / Europe / History / 19th century; Agricultural innovations / Europe / History / 20th century; Wissenschaftstransfer; Ländlicher Raum; Know-how; Landwirtschaft; Europa; Aufsatzsammlung